Management and the prevention of anaemia in pregnancy (2023)
Anaemia during pregnancy is a significant public health concern in this country. With 40% of the population living in poverty and 63% facing multidimensional poverty as reported by the National MPI 2022, it is not surprising that women often have poor diets, making them more prone to iron and folate deficiency anaemia, which are the leading causes of anaemia during pregnancy. Other factors contributing to anaemia during pregnancy include having multiple pregnancies in quick succession, giving birth to multiple babies, pre-pregnancy menorrhagia, worm infestation, severe and prolonged hyperemesis gravidarum, among others. Anaemia during pregnancy can cause serious complications for the fetus, such as preterm birth and low birth weight. It can also affect the mother's well-being, with severe anaemia increasing the risk of death or near misses. Recent evidence also suggests that anaemia during pregnancy significantly increases the risk of postpartum haemorrhage caused by uterine atony. It's crucial for healthcare providers to be aware of the issues associated with anaemia during pregnancy and the measures for preventing and detecting high-risk pregnancies early. Healthcare providers must understand the different types of anaemia, common symptoms, and treatment options to recognize the warning signs of anaemia and avoid complications. This clinical guideline is designed for obstetricians and midwives to help manage pregnant women with anaemia appropriately. The document's layout and practical step-by-step approach to managing anaemia during pregnancy are commendable, and the team of experts who produced this high-quality document under the chairmanship of Prof Abiodun Aboyeji deserves appreciation. All members of the committee deserve commendation for a job well done. Healthcare practitioners should use this guideline to manage anaemia during pregnancy effectively, reducing complications for both mother and foetus, and ultimately reducing the burden of high maternal and perinatal mortality and morbidity related to anaemia. This is one of four clinical guidelines to be produced by the SOGON Executive under my leadership. The other three will be rolled out shortly.